Estudio reactivación de la oferta exportadora del Valle del Cauca luego de la pandemia por Covid -19 - Meneses Zambrano, Lisbeth Brigitte (Universidad Antonio Nariño, 2023)
The objective of this monograph is to analyze the factors that have allowed the reactivation of the export supply of Valle del Cauca after the Covid-19 pandemic. For this, a documentary review was carried out based on documents from national authorities such as the Ministry of Industry, Tourism and Commerce, DANE, Gobernación del Valle, unions, among others. In the results, the trade balance of the Valley was evidenced, which was not significantly affected during the year 2020, where the most severe effects are experienced by the measures to stop the Covid19 pandemic.